Analisis Dampak Perceraian Anak Terhadap Keluarga (di Desa Cililitan Kecamatan Picung) - Warsih, Warsih; Irodat, Ahsan; Mustafid, Hidayat (Posita: Jurnal Hukum Keluarga Islam, 2025)
This study aims to explore the factors contributing to divorce and formulate effective solutions for resolving domestic conflicts in Cililitan Village, Picung District. Utilizing a descriptive qualitative approach, data were collected through in-depth interviews with five women who experienced divorce between 2022 and 2024. The findings reveal that the primary causes of divorce in this area are ongoing disputes and prolonged financial pressures. The impact of divorce is not only felt by the couples but also by their children, who suffer from psychological distress, and by the mothers, who often bear the emotional and financial burdens of raising their children alone. As a preventive effort, active involvement of all family members is essential in building a healthy and harmonious relationship. Open communication, mutual understanding, compromise, and respect for personal boundaries are key to fostering family resilience. In addition, emotional management skills and the willingness to seek professional support are crucial steps to maintaining family unity and preventing divorce.